2006
DOI: 10.1099/vir.0.81452-0
|View full text |Cite
|
Sign up to set email alerts
|

Human cytomegalovirus modulation of CCR5 expression on myeloid cells affects susceptibility to human immunodeficiency virus type 1 infection

Abstract: For some time there has been evidence suggesting an interaction between human cytomegalovirus (HCMV) and Human immunodeficiency virus (HIV) in the pathogenesis of AIDS. Here, the interaction of HCMV and HIV-1 was examined in monocyte/macrophage cells, two cell types known to be targets for both viruses in vivo. Infection experiments demonstrated that prior infection with HCMV impeded subsequent superinfection with HIV-1. In contrast, uninfected bystander cells within the population were still permissive for HI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 41 publications
1
16
0
Order By: Relevance
“…However, although porcine IL-8 binds human leukocytes, its potential effect on human leukocyte chemotaxis is a matter of debate (57,58). Together with previous studies, our data stress the importance of soluble factors released from infected cells that contribute to an amplification of the immune and inflammatory response (15,16,59,60). Furthermore, HCMV induced apoptosis in HCMV-infected pEC cultures (Millard, unpublished data).…”
Section: Discussionsupporting
confidence: 74%
“…However, although porcine IL-8 binds human leukocytes, its potential effect on human leukocyte chemotaxis is a matter of debate (57,58). Together with previous studies, our data stress the importance of soluble factors released from infected cells that contribute to an amplification of the immune and inflammatory response (15,16,59,60). Furthermore, HCMV induced apoptosis in HCMV-infected pEC cultures (Millard, unpublished data).…”
Section: Discussionsupporting
confidence: 74%
“…It is related to numerous conditions in this group, including ocular CMV disease, immune reconstitution syndrome, gastrointestinal disease, encephalitis and pneumonia, and mortality [36]. Furthermore, there is increasing evidence of an association between the presence of 4 and enhanced risk of HIV-related dementia [3,37,38]. Our results suggest that 4 is a factor that influences CMV IgG antibody levels.…”
Section: Crp In the Pathway Between 4 And CMVmentioning
confidence: 70%
“…Moreover, CMV can activate HIV latent provirus,45 alter the tropism of HIV,46 encode an alternative receptor for HIV,47 and act as a cofactor enhancing progression of AIDS even in the era of HAART 10, 48. Yet, a recent observation showed that CMV- infected cells can secrete soluble factors that are able to increase CCR5 surface expression on uninfected bystander cells 49. One can speculate that the CCR5 +.p1.+ promoter haplotype associated with increased CCR5 expression may be upregulated further due to CMV activation, making immune cells more susceptible to HIV-1 infection.…”
Section: Discussionmentioning
confidence: 99%